Stable isotopes reveal that gelatinous zooplankton diets group by taxonomy and feeding traits in a coastal upwelling system - Elizabeth Wallace; Luke A. Bobay; Lucas C. R. Silva; Su Sponaugle; Robert K. Cowen; Kelly R. Sutherland (Limnology and Oceanography, 2026)
Gelatinous zooplankton are abundant in marine ecosystems, yet their trophic roles and functional diversity in food webs have only recently gained attention. Gelatinous zooplankton taxa including hydromedusae, ctenophores, siphonophores, chaetognaths, and pelagic tunicates span multiple phyla and are often grouped taxonomically, but trait‐based categorizations have emerged as an ecologically meaningful alternative. Considering their wide variety of diets and feeding modes, we examined whether gelatinous zooplankton diet diversity can be described by feeding mode or phylum categorizations. We analyzed the carbon and nitrogen stable isotope composition (δ 13 C and δ 15 N values) of 490 gelatinous zooplankton samples of 32 genera/species collected across seasons and shelf positions in the northern California Current ecosystem. The δ 13 C and δ 15 N values fell into distinct groups when taxa were categorized three ways—by phylum, feeding mode, and feeding anatomy—indicating that both taxonomic and trait‐based approaches are useful for describing the trophic diversity of gelatinous zooplankton. Even when gelatinous specimens cannot be identified taxonomically, their diets likely resemble those of taxa sharing the same feeding mode or anatomy. These insights refine our knowledge of marine food webs and facilitate the incorporation of these ubiquitous members of the food web into ecosystem models.